Social media, migration and the platformization of moral panic: Evidence from Canada. (June 2023) - Walsh, James P; Hill, Dallas
As a contentious issue affecting the character, boundaries and future of social order, migration represents a recurrent source of moral panic. While analysts have considered conventional outlets' role in triggering collective alarm, less is known about social media's effects on migration's construction as a social problem. Working with an original dataset of tweets from the 2019 Canadian election, a period of heightened concern and outcry for significant portions of the electorate, this paper employs content analytic methods to assess migration's online demonization and interrogate the patterns of framing, participation and engagement brought within the issue's orbit. Alongside documenting significant disquiet and antipathy, its findings suggest that Twitter is transforming panic production and facilitating forms of reaction involving mass-participation and collaboration; interference from automated 'bots' and considerable dispute, dissent and negotiation. Based on these results, the sensitizing concept of platformed panics is proposed to capture how social media's technical affordances, design and appropriation align to promote moral panics that are networked, algorithmic and contested.